The Impact of Corporate Governance and Capital Structure on Firm Performance: Evidence from UK - Zhuang, Xi (2013)
Abstract This study examines the impact of corporate governance and capital structure on companies’ performance using a comprehensive sample from 181 non-financial and non-utilities companies listed in the UK during the period 2004-2012. Three panel data linear regression models have been used to explore the relationships between corporate governance, capital structure and firm performance. Firm performance is measured in terms of Tobin’s Q. Corporate governance variables identified as probably explaining a significant amount of variations in company’s performance include CEO Duality, board size, independent board members and highest remuneration package. Capital structure variables identified as probably explaining a significant amount of variations in company’s performance include leverage, growth, firm size and profitability. Results from this study shows corporate governance has an influence on firm performance, but is not the only factor. The results also suggest that corporate governance and capital structure variables except for CEO duality and growth have a significantly joint affect on firm’s performance.